Carreiras de professoras das Ciências Exatas e Engenharia: estudo em uma IFES do Nordeste brasileiro - Silva, Lucimeiry Batista da (2017)
This study aimed to analyze the process of sexual division of labor and gender relations that shape the professional trajectories of female teachers in the courses of Mechanical Engineering, Physics and Mathematics, considered the most masculine in a Federal Institution of Higher Education of the Brazilian Northeast. Some questions guided this research: how are drawn both the professional and life trajectories of female teachers in male areas? How did gender relations affected the careers of these college professors? Based on the assumption that there is hierarchy, prestige and status in the distribution of academic activities between men and women, how do these divisions occur in the departments researched? Do these teachers perceive gender and sex discrimination in the relationship with co-workers and students? In order to understand the central subject of the study, I reviewed its theoretical foundation, addressing studies on women in academy, especially in the departments where they are a minority, highlighting the literature on gender, sexual division of labor, habitus, culture and academic field. As evidence, narrative interviews were conducted with eleven female teachers from those areas were carried out. In this qualitative investigation, the narratives gave support to the construction those teachers’ biographies and discourse analysis was used as a tool to support the analysis of the data. The results indicate that there are obstacles in the career development of these women teachers who do not occupy prestige and power spaces in respective areas. In the relationship with male pairs and students, both career and teachers’ behavior are influenced by gender division as well as by male habitus in the academic field. In addition, it has been observed that it is difficult for the interviewees to balance work and family life, since the domestic tasks and care for the family continue to be an obstacle to the full professional development of women. This research concluded that these teachers, despite a solid academic background, some with more than one postdoctoral degree, are kept out of the center of production and academic prestige. Thus, it is evident that the relations of male domination are far from being abolished from the academy. Finally, some recommendations were presented, aiming to contribute to the development of research involving knowledge in the area of gender studies, academic careers and labor relations, and on the relationships between men and women in the context of Brazilian higher education.